MATHEMATICAL ANXIETY AMONG ENGINEERING STUDENTS - Prahmana, Rully Charitas Indra; Sutanti, Tri; Wibawa, Aji Prasetya; Diponegoro, Ahmad Muhammad (IKIP Siliwangi and I-MES, 2019)
Mathematical anxiety has a negative relationship with mathematics performance and achievement. Further explained, mathematics anxiety has an indirect effect on mathematics performance. This research explores sources or factors related to mathematics anxiety among engineering students at a private university in Indonesia. A total of 47 engineering students participated in this survey that randomly chosen based on gender, major, and age. Two main factors are affecting the mathematics anxiety of engineering students, namely internal and external factors. The results show that mathematics anxiety among engineering students is manifested into three aspects. Firstly, the home aspects are talking about the influence of parents and sibling. Secondly, society's issues are discussing self-efficacy, social reinforcement to hate mathematics, and social stereotypes. Lastly, the classroom aspects are talking about the traditional mathematics learning process and classroom culture, namely the experience of learning mathematics in classrooms and relationships between friends during learning. The details of the statements under the aspects also highlight unique problems and are not covered by previous research in mathematical anxiety. Next, differences in mathematics anxiety by gender and faculty were examined.